الارتباط التشكيلي للصورة المرئية وتوظيف الميكانزمات الدلالية لها - الضاويد. بشير محمد (Aljameai, 2026)
المستخلص: يسعى التشكيل البصري والجمالي للمتلقي من خلال مقاربة أهم المفاهيم والمصطلحات ذات العلاقة المباشرة بخطه واقتراح مجموعة من الإجراءات العملية والممارسات النصية لتحليل العمل الفني وإعادة تركيبه على قاعدة سيميوطيقية صلبة تأخذ بعين الاعتبار أنواع القراءة وسياق القراءة وفضاءاتها المتعددة وزمن الإبداع ونوعيته ، ويفترض وجود مادة إبداعية بين الصورة ومتلقيها مثل قناة التواصل بين المبدع وقاري ما ابتدعه المبدع ، قد تكون المادة منظومة تدخل ضمن نسيج الإبداع القولي كالشعر والنثر وفنون الرد اللفظي ، أو مرئية ذات طبيعة أيقونية ومادية كالصور والأعمال الدرامية ، واللوحات التشكيلية ، وغيرها من الوسائط التعبيرية البصرية والعوامل الثقافية المتعددة ، فالنص التشكيلي البصري يعد بالضرورة الإبداعية عملا فنياً ، كما أنه ليس وسيلة يعبر الفنان عن نفسه فحسب بل هو وسيلة كذلك تستشير وتوجه في المشاهد نوعا من الخبرة الجمالية وتتوجه إلى حاسته البصرية أو السمعية أو الاثنين معا نشير بالتالي استجابات أخرى كالخيال والفهم والعاطفة ، والمكانيزمات فهي الآليات أو أدوات أو وسائل تنتج لبناء الصورة الدرامية داخل العمل الفني وهي طرق يستخدمها المخرج لتشكيل المعني البصري والرمزي للصورة. Abstract: The visual and aesthetic formation seeks to engage the recipient through approaching the most important concepts and terminologies directly related to its discourse, while proposing a set of practical procedures and textual practices for analyzing and reconstructing the artwork upon a solid semiotic foundation that takes into account the types of reading, the context of reading, its multiple spaces, the time of creativity, and its quality. It assumes the existence of a creative medium between the image and its recipient, similar to the communication channel between the creator and the reader of what the creator has produced. This medium may consist of a system embedded within the fabric of verbal creativity such as poetry, prose, and the arts of verbal expression, or it may be visual in nature, possessing iconic and material characteristics such as images, dramatic works, plastic arts, and other visual expressive media and diverse cultural factors. Thus, the visual plastic text is necessarily considered a creative artistic work. It is not merely a means through which the artist expresses himself, but also a medium that evokes and directs within the viewer a kind of aesthetic experience, addressing the visual sense, the auditory sense, or both together, thereby stimulating other responses such as imagination, understanding, and emotion. As for mechanisms, they are the tools, methods, or means employed in constructing the dramatic image within the artwork. They are the techniques used by the director to shape the visual and symbolic meaning of the image.